2014
DOI: 10.1007/s13762-014-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

A new two-step screening method for prospecting of trace element accumulating plants

Abstract: A vulnerable point of the currently used approach to the search for the new species capable of abnormal accumulation (hyperaccumulation) of trace elements is that most studies have been conducted in laboratory conditions and focused on the determination of a limited number of elements. We propose a methodology that enables screening for multi-element accumulating plants. This methodology is based on two analytical steps: a semiquantitative analysis mode by ICP-MS that allows selection of plant samples which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In cases where the obtained concentrations of the PTEs are close to the maximum permitted values, their determination with a quantitative method for higher accuracy could be applied. Similar recommendations have already been made for analysis of plant [31] and soil samples [39]. Thus, it proves that the TotalQuant method is a suitable approach for a quick assessment of the possibility of sludge application to agriculture with satisfactory accuracy.…”
Section: Applicability Of the Methods For Analysis Of Sewage Sludge S...supporting
confidence: 73%
See 1 more Smart Citation
“…In cases where the obtained concentrations of the PTEs are close to the maximum permitted values, their determination with a quantitative method for higher accuracy could be applied. Similar recommendations have already been made for analysis of plant [31] and soil samples [39]. Thus, it proves that the TotalQuant method is a suitable approach for a quick assessment of the possibility of sludge application to agriculture with satisfactory accuracy.…”
Section: Applicability Of the Methods For Analysis Of Sewage Sludge S...supporting
confidence: 73%
“…The TotalQuant method finds application due to the serious advantages it provides as an opportunity to obtain quantitative data for a large number of elements at a very high speed, low consumption of reagents and energy, and less analytical waste, which makes it cheaper and greener [27,28]. The method has been applied for analysis of water samples [23,26,29], plants [30,31], soils [32,33], air particles [34], biological samples [24], geological samples [35], et al The published data for the accuracy vary widely and may depend on the concentration range of the elements, the matrix, the measured mass, etc. Usually, the quantitative analysis is characterized with very good accuracy, better than 10% [26], whereas the accuracy of the TotalQuant method is worse, and varies within quite wide limits, from below 10% [24,26,30] to 30-50% [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research aiming plant communities in ultramafic areas are focused mostly on Ni-hyperaccumulators referred as species with Ni content of at least 1000 mg kg −1 in the dry matter of leaves i.e. Pycnandra acuminata (Reeves 1992;Reeves and Baker 2000;Reeves et al 2007a; Van der Ent et al 2013a;Gałuszka et al 2015; Van der Ent et al 2015). Furthermore, some Nihyperaccumulators give opportunity in phytomining operations because of high content of Ni and relatively high biomass (Nkrumah et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Barium concentration in topsoil (0–30 cm) in Balin ranges from 30 to 240 ppm (Pasieczna 2011 ); whereas Ba content in topsoil in the vicinity of Żywiec is generally less than 50 ppm (Lis and Pasieczna 1995 ). While plants are known to accumulate Ba in their green parts (Kabata-Pendias and Pendias 1999 ; Gałuszka et al 2015 ), and food ingestion was identified as the primary exposure to Ba (ATSDR Agency for Toxic Substances and Disease Registry 2007 ), this intake route cannot explain the difference in Ba concentrations in antlers from the Balin and Żywiec areas.…”
Section: Resultsmentioning
confidence: 99%